Performance Studies of Natural Rubber/Organomodified Kaolin Vulcanizates Developed for Tire Sidewall Applications - Mgbemena, C. O.; Mgbemena, C. E. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
This study aims at evaluating the performance of Natural Rubber/organomodified kaolin vulcanizates to ascertain its suitability for tire sidewall applications. The cure characteristics, filler dispersion, tensile and tear properties and De-Mattia flex fatigue characteristics of natural rubber (NR) filled with 2-10 phr of Rubber Seed Oil (RSO), and Tea Seed Oil (TSO) modified kaolin developed specifically for tire sidewall applications were assessed. The NR compounds containing RSO and TSO modified kaolin showed lower optimum cure time (t90 at 150°C) as against that containing the same dosage of unmodified kaolin. The results show significant increases in tensile modulus, tensile strength and tear strength for the NR vulcanizates containing the organomodified kaolins, compared to vulcanizates containing unmodified kaolin. TSO modified kaolin vulcanizates at 6phr showed better resistance to crack initiation and flex fatigue failure. The SEM and AFM micrographs of the vulcanizates containing organomodified kaolins also showed an excellent uniform dispersion of the filler particles in the NR matrix. The results obtained for Natural Rubber/Tea Seed Oil modified kaolin vulcanizates at 10phr shows a short optimum cure time, high maximum torque, better tear strength, excellent resistance to crack initiation and flex fatigue behaviour. These indicate that the Natural Rubber/Tea Seed Oil modified kaolin vulcanizates are preferred materials for tire sidewall applications.